Optimisation Processes in Tidal Analysis - Murray, M. T. (The International Hydrographic Review, 2015)
An analysis of tidal observations is normally carried out, not as an end in itself, but in order to obtain data which can be used to prepare future tidal predictions. The best form of analysis is that which yields the constants producing the best future predictions. Since the future is not known, this condition cannot be used as the basis of an analysis method; the condition which can be used, however, is that the best form of analysis yields those constants which can hindcast the year of analysis most accurately. It is this concept of a “ best fit ” between the tidal observations and the predictions obtained from the analysis results which deserves examination. The examples considered in this paper will all refer to the analysis of hourly heights of tide; the principles concerned would, however, apply equally well to the analysis of other tidal characteristics.